2020
DOI: 10.1016/j.heliyon.2020.e03606
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and antimicrobial resistance profile of coagulase-negative staphylococci from cattle, equipment, and personnel on dairy farm and abattoir settings

Abstract: Background: Safe food is central to social wellbeing. Coagulase-negative staphylococci (CNS) are a threat to food safety because they may harbor multiple enterotoxins and antimicrobial resistance (AMR) genes. CNS bacteria are an emerging nosocomial pathogen in public health. CNS also cause bovine mastitis with a significant economic loss in the dairy industry and may introduce toxins to the food supply chain resulting in foodborne illnesses. However, information on CNS and their AMR status are scarce in food a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 81 publications
(106 reference statements)
2
13
7
Order By: Relevance
“…Another interesting nding in this research was that the highest AMR was found in isolates from humans and the environment, mainly against penicillins, cefoxitin, erythromycin and tetracyclines, being signi cantly higher in S. aureus. These results are similar to those reported in NAS and MRSA of human and environmental origin in dairy farms in different countries (Visciano et al 2014;Gizaw et al 2020). Other studies have found that isolates of S. aureus and NAS from environmental sources (milking parlor, canteens, cooling tank, among others) and from humans share the same AMR and virulence pro le with strains isolated from milk of cows with mastitis (Farias et al 2018;Krukowski et al 2020).…”
Section: Discussionsupporting
confidence: 91%
“…Another interesting nding in this research was that the highest AMR was found in isolates from humans and the environment, mainly against penicillins, cefoxitin, erythromycin and tetracyclines, being signi cantly higher in S. aureus. These results are similar to those reported in NAS and MRSA of human and environmental origin in dairy farms in different countries (Visciano et al 2014;Gizaw et al 2020). Other studies have found that isolates of S. aureus and NAS from environmental sources (milking parlor, canteens, cooling tank, among others) and from humans share the same AMR and virulence pro le with strains isolated from milk of cows with mastitis (Farias et al 2018;Krukowski et al 2020).…”
Section: Discussionsupporting
confidence: 91%
“…The consumption of milk in Ethiopia was reported to be between 17 and 19 liters per capita, which is lower than the regional average (for instance, the amount of milk consumed per capita in Uganda and Kenya is 50 and 90 liters, respectively) [ 12 ]. The production of milk in the country is lower than the requirement, and this might be due to versatile factors; including diseases, improper production of dairy animals, and milk processing practices in farms [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“… 10 The CNS is of great importance due to its multidrug resistance nature. 12 In addition, studies showing the specific species of CNS in Ethiopia are scarce. Therefore, the current study was conducted with the objectives of estimating the prevalence of mastitis, assessment of potential risk factors associated with Zebu ( Bos indicus ) cows’ mastitis, isolation, and identification of Staphylococcus species, and determination of the antimicrobial susceptibility of the Staphylococcus aureus and CNS isolates.…”
Section: Introductionmentioning
confidence: 99%